GerenciaDOR™: development of digital technology by nurses for the assessment of patients with chronic pain - Bianca Ferreira da Silva Brandão; Eliseth Ribeiro Leão (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to develop a digital technological solution (prototype) for assessing patients with chronic pain. Methods: this is a methodological and technological development study based on the Human-Centered Design framework and the principles of Patient-Centered Care. The prototype guides patients through a body diagram and directs them to an evaluation using specific instruments that address the multidimensional aspects of chronic pain. Results: the GerenciaDOR* project enables navigation through the Web App screens, providing access to pain assessment features up to the presentation of results. Final Considerations: the study describes a systematic approach to pain assessment and expands nurses’ knowledge in pain management. Additionally, it can promote the development of other digital technologies for chronic pain assessment and contribute to a multidisciplinary, patient centered treatment.